IMF Survey, Volume 36 Issue 12. (IMF Survey; IMF Survey ;, 2007)
Global market turmoil; Strauss-Kahn to head IMF; Global warming; Europe: Financial integration; Islamic finance; Emerging market vulnerability; Subprime turmoil: Lessons; Maghreb integration; Oil producers: Fiscal management; News briefs.